The Protective Role of Forestry to the Land - Ghosh, R. C. (Indian Forester, 1975)
Historically, forestry was dedicated to, and developed for protection and conservation. In fact, the foresters were the original environmentalists. But the dynamics of conversion from predominantly rural and agricultural society to an industrial structure with urban amenities, has given rise to a host of unanswered questions that are fundamental to working out future management policies that would take into account the rapidly developing social consciousness to rational use of natural resources. Much of the forests in this country is situated in the sensitive areas of catchments of many important rivers and it is not by chance that success of national development plans of high priority such as for water development, irrigation, power production or flood protection depend on the stability or improvement of these areas. Nevertheless, the fact remains that forestry cannot discard its utilitarian outlook. As professional resource managers, foresters thus bear a heavy burden and have to recognise seemingly contrasting values of production and protection that forests and forestry contribute to the welfare system or a rapidly developing society. A reinterpretation of the goals and status of forestry in the framework of land utilisation is necessary to replace the concept of autonomous role of forestry based on the production function alone. The new implica tions have to be studied in great details to judge the propriety of the management alternatives and finally choose the one that would cater or, apart from wood, many other amenities that are bountiful in a stable situation. In the face of this, it would be worthwhile considering if the management economy can take one or more adjustments at a time.